ENZYMES AND APPROACHES TO THEIR APPLICATION IN THE LEATHER PRODUCTION - KOPYTINA, Iryna; ANDREYEVA, Olga; MOKROUSOVA, Olena; OKHMAT, Olena (Herald of Khmelnytskyi National University. Technical sciences, 2022)
In a market economy, the leather industry faces new challenges, including the need to improve and optimize technological processes to achieve the required quality of final products and comply with environmental legislation. The practical experience and long-term achievements of the authors in the field of natural leather production indicate the importance of choosing the right method and materials for processing raw and semi-finished hides. One proven solution is the use of enzymes. Based on the results of the analysis of literary sources, information on traditional ideas about enzymes and approaches to their use in the production of natural leather is systematized.According to established ideas, enzymes are not just organic substances, proteins, but also high-speed catalysts for multiple chemical and biochemical reactions. Preparations based on enzymes have been commercially studied in detergents, food, light, pharmaceutical, diagnostic, chemical and other industries, in the agro-industrial complex. This prevalence is explained by the fact that the use of these funds contributes to improving the quality of products, culture and the level of greening of production, more rational use of raw materials and material resources. In the leather industry, enzymatic processes have gone through a long evolutionary path - from the use of primitive improvised means to the use of preparations that are more up to date with the requirements of the time. According to the modern classification, enzymes are divided into six main classes according to the nature of the catalyzed reaction. In the manufacture of genuine leather, taking into account the nature of the substrate (proteins, carbohydrates, lipids), preparations based on enzymes are used that belong to the class of hydrolases (proteases, amylases, lipases) and differ from each other in the active center and mode of action. The preparations used can either accelerate processes that usually proceed slowly (soaking), or provide a specific transformation of raw material (bating), or replace known chemical reagents (unhairing). The results obtained will be taken into account in the future when studying innovative approaches to the enzymization of leather production.
Keywords: traditional representations and approaches; enzymes; technological processes; genuine leather